Nighttime OClO in the winter Arctic vortex - Canty, T.; Riviere, E. D.; Salawitch, R. J.; Berthet, G.; Renard, J.-B.; Pfeilsticker, K.; Dorf, M.; Butz, A.; Bosch, H.; Stimpfle, R. M.; Wilmouth, D. M.; Richard, E. C.; et al. (Journal of Geophysical Research, 2008)
We show that a nighttime profile of OClO in the Arctic vortex during the winter of 2000 is overestimated, by nearly a factor of 2, using an isentropic trajectory model constrained by observed profiles of ClOx (ClO + 2 X ClOOCl) and BrO. Calculated abundances of nighttime OClO are shown to be sensitive to the abundance of BrOx (BrO + BrCl), details of the air parcel history during the most recent sunrise/sunset transitions, and the BrCl yield from the reaction BrO + ClO. Many uncertainties are considered, and the discrepancy between measured and modeled nighttime OClO appears to be robust. This discrepancy suggests that production of OClO occurs more slowly than implied by standard photochemistry. If the yield of BrCl from the reaction of BrO + ClO is increased from 7% (JPL 2002 value) to 11% (near the upper limit of the uncertainty), good agreement is found between measured and modeled nighttime OClO. This study highlights the importance of accurate knowledge of BrO + ClO reaction kinetics as well as air parcel trajectories for proper interpretation of nighttime OClO. These factors have a considerably smaller impact on the interpretation of OClO observations obtained during twilight (90° ≤SZA ≤ 92°), when photolytic processes are still active. NASA/JPL